Neurotic Trends Among Individuals in Early Adulthood Who Experience Emotional Abuse in Dating Relationships: [Tren Neurotik Pada Individu Dewasa Awal yang Mengalami Kekerasan Emosional Dalam Hubungan Berpacaran] - Kristhi, Nathasya Shesilia; Sukmaningrum, Evi (ANIMA Indonesian Psychological Journal, 2023)
One of many issues in dating relationships is physical or emotional abuse. This issue becomes complicated as this relationship form is often not legally bound. In addition, dating violence is often associated with men as perpetrators and women as victims. Using Horney’s classical theory, the authors aim to explain the personality dynamics of individuals in early adulthood who experience emotional abuse in dating relationships. This study applied a phenomenological qualitative approach. The technique utilized to obtain data was through questionnaires, interviews, and online observations of four participants (one male perpetrator, one male victim, one female perpetrator, and one female victim), whereby each participant was unrelated to each other. A thematic analysis found that participants who were perpetrators of emotional abuse in dating relations had a tendency towards the aggressive type of neurotic trend, based on the need to control and exploit other parties. The dynamics formed in this relationship are behaviors related to controlling and excessive monitoring of partners, silent treatment and avoidance, and intimidating and threatening the partner. Meanwhile, the victims of emotional abuse in dating relationships tend have a tendency towards the compliant type of neurotic trend, that is seen from the need to receive affection, and to have a partner who is powerful and has control over themselves. The dynamics that are formed in this relationship comprise behaviors that tolerate the perpetrator's attitude to survive the relationship, as the victims do not want to lose affection, are still dependent on the perpetrator, and feel that they must concede. Salah satu permasalahan dalam hubungan berpacaran adalah kekerasan dalam hubungan berpacaran, baik secara fisik maupun emosional. Permasalahan ini menjadi rumit karena bentuk relasi ini seringkali tidak terikat secara hukum. Selain itu, kekerasan dalam berpacaran seringkali diasosiasikan bahwa laki-laki merupakan pelaku kekerasan dan perempuan adalah korban. Dengan pendekatan teori klasik Horney, penulis ingin menjelaskan dinamika kepribadian individu dewasa awal yang memiliki pengalaman kekerasan emosional dalam hubungan berpacaran. Studi ini menggunakan pendekatan kualitatif fenomenologis. Teknik yang digunakan untuk memperoleh data adalah dengan menggunakan kuesioner, wawancara, observasi secara daring terhadap empat partisipan (satu laki-laki sebagai pelaku, satu laki-laki sebagai korban, satu perempuan sebagai pelaku, dan satu perempuan sebagai korban), serta setiap partisipan bukan pasangan. Hasil studi melalui analisis tematik menemukan bahwa partisipan sebagai pelaku kekerasan emosional dalam hubungan berpacaran memiliki kecenderungan tren neurotik aggressive type yang didasari kebutuhan untuk mengendalikan dan eksploitasi pihak lain. Dinamika yang terbentuk dalam relasi tersebut adalah perilaku mengontrol atau mengawasi pasangan, merendahkan dan memaki pasangan, mendiamkan dan menghindari pasangan, serta mengintimidasi dan mengancam pasangan. Sementara itu, korban kekerasan emosional dalam hubungan berpacaran memiliki kecenderungan tren neurotik compliant type yang didasari kebutuhan memperoleh afeksi, mendapatkan pasangan yang berkuasa dan memegang kendali atas dirinya. Dinamika yang terbentuk dalam relasi tersebut adalah perilaku untuk mentoleransi sikap pelaku dan bertahan dalam hubungan karena tidak ingin kehilangan kasih sayang, bergantung pada pelaku, dan merasa dirinya harus mengalah.